Serum and Cervicovaginal Fluid Antibody Profiling in Herpes Simplex Virus–Seronegative Recipients of the HSV529 Vaccine. (15th March 2021) - Wang, Kening; Dropulic, Lesia; Bozekowski, Joel; Pietz, Harlan L; Jegaskanda, Sinthujan; Dowdell, Kennichi; Vogel, Joshua S; Garabedian, Doreen; Oestreich, Makinna; Nguyen, Hanh; Ali, Mir A; Lumbard, Keith; et al.
Abstract: Previous herpes simplex virus type 2 (HSV-2) vaccines have not prevented genital herpes. Concerns have been raised about the choice of antigen, the type of antibody induced by the vaccine, and whether antibody is present in the genital tract where infection occurs. We reported results of a trial of an HSV-2 replication-defective vaccine, HSV529, that induced serum neutralizing antibody responses in 78% of HSV-1 – /HSV-2 – vaccine recipients. Here we show that HSV-1 – /HSV-2 – vaccine recipients developed antibodies to epitopes of several viral proteins; however, fewer antibody epitopes were detected in vaccine recipients compared with naturally infected persons. HSV529 induced antibodies that mediated HSV-2–specific natural killer (NK) cell activation. Depletion of glycoprotein D (gD)–binding antibody from sera reduced neutralizing titers by 62% and NK cell activation by 81%. HSV-2 gD antibody was detected in cervicovaginal fluid at about one-third the level of that in serum. A vaccine that induces potent serum antibodies transported to the genital tract might reduce HSV genital infection. Abstract : Recipients of a herpes simplex virus type 2 (HSV-2) vaccine trial had antibodies to fewer viral epitopes compared with natural infection, HSV gD antibodies in cervicovaginal fluid at one-third the level of those in serum, and antibodies that mediated HSV-2–specific natural killer cell activation.